The System of Transitivity in the War on Terror Discourse - Hampl, Marek (Communications - Scientific letters of the University of Zilina, 2014)
The paper focuses on the presentation of social actors in the discourse of George W. Bush in the period from October 2001 to March 2003. The first part of the paper deals with the theoretical elaboration of the system of transitivity within M. A. K. Halliday´s Systemic Functional Linguistics (SFL). In this part of the article, the relevant components of the system of transitivity are introduced and discussed. The focus of the analytical part of the paper is on the representation of social actors in the discourse of the speaker. The aim of the paper is to observe the creation of the “Us“ and “Them“ camps with the help of the selections in Material processes.